Microbial interactions on manganese availability and uptake by soybean - Nogueira, Marco Antonio; Cardoso, Elke Jurandy Bran Nogueira (Pesquisa Agropecuaria Brasileira, 2002)
<!--[if gte mso 9]> Normal 0 <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> The aim of this work was to evaluate the effect of the interaction between arbuscular mycorrhizal fungi and the soil microbial community, on the Mn availability, uptake, and Mn toxicity alleviation in soybean. Plants were inoculated with Glomus etunicatum or G. macrocarpum, with or without the microbial community re-establishment after autoclaving. A non-mycorrhizal treatment had the re-establishment of the soil microbial community, whilst other was kept as absolute control. Mycorrhizal plants had more growth and less Mn toxicity, mainly when the microbial community was re-established. In that case there was an increase in Fe availability and decrease in Mn availability in the substrate. Shoot P concentration was higher in the mycorrhizal plants. There was lower Fe and Mn concentration in the shoots of mycorrhizal plants, more intensively when the microbial community was re-established. In the roots, this behavior was the same for Mn and inverse for Fe. The Mn decrease in the shoots was attributed to the decrease of its availability, whilst the decrease of Fe concentration in the shoots was attributed to its retention in the roots.